Pengaruh Implementasi Kurikulum Merdeka Belajar terhadap Hasil Belajar Fiqih Siswa Kelas VIII di MTsN 16 Jombang - M, Nur Afifah Utsfiyul; Waslah, Waslah; Huda, Saihul Atho Alaul (Lembaga Yasin AlSys, 2025)
The modifications to the education curriculum in Indonesia are driven by a variety of factors, such as socio-political dynamics, governmental policies, and assessments of the previous curriculum. The Covid-19 pandemic has intensified educational challenges, resulting in a learning crisis referred to as Learning Loss. This research aims to investigate the impact of the Merdeka Belajar Curriculum on students' learning outcomes in Fiqh subjects. A quantitative method with a causal approach and an asymmetrical relationship model was employed for this study. Participants were chosen using the Simple Random Sampling method, and data were gathered through questionnaires and documentation. The analysis of the data was performed using simple linear regression. The findings, analyzed with SPSS 25, indicated that hypothesis testing via simple linear regression yielded a significance value of 0.008 (<0.05) and a t-value of 2.800 (> t-table 1.684) at a 5% significance level. This result demonstrates a positive and significant correlation between the implementation of an independent learning curriculum and student learning outcomes. Furthermore, the contribution of the independent curriculum implementation variable (X) to the Fiqh learning outcomes variable (Y) was found to be 0.167 or 16.7% (R square), with the remaining influence attributed to other factors not investigated by the author.